2009
DOI: 10.1002/bip.21299
|View full text |Cite
|
Sign up to set email alerts
|

Viral structural transition mechanisms revealed by multiscale molecular dynamics/order parameter extrapolation simulation

Abstract: On the basis of an all-atom multiscale analysis theory of nanosystem dynamics, a multiscale molecular dynamics/order parameter extrapolation (MD/OPX) approach has recently been developed. It accelerates MD for long-time simulation of large bionanosystems and addresses rapid atomistic fluctuations and slowly varying coherent dynamics simultaneously. In this study, MD/OPX is optimized and implemented to simulate viral capsid structural transitions. Specifically, 200 ns MD/OPX simulation of the swollen state of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 62 publications
3
46
0
Order By: Relevance
“…Collectively, the experimental results presented here complement the multi scale molecular dynamics simulations of Miao and Ortoleva [15]. Their studies showed that structural transitions in viral capsids begin locally then propagate across the continuum of the outer protein layer.…”
Section: D Reconstructions Reveal a Continuum Of Features That Represupporting
confidence: 72%
See 1 more Smart Citation
“…Collectively, the experimental results presented here complement the multi scale molecular dynamics simulations of Miao and Ortoleva [15]. Their studies showed that structural transitions in viral capsids begin locally then propagate across the continuum of the outer protein layer.…”
Section: D Reconstructions Reveal a Continuum Of Features That Represupporting
confidence: 72%
“…Their findings also support the idea of non symmetric intermediate states among ordered, icosahedral viral assemblies. In particular, they suggested that the use of symmetry elements alone does not reveal the full regime of viral structural transitions [15].…”
Section: D Reconstructions Reveal a Continuum Of Features That Reprementioning
confidence: 99%
“…In the present study, we found Legendre polynomials to be convenient for simulating systems with closed boundaries of rectangular geometry. 4,6,8,9 In our approach, points r within the system are considered to be a displacement of original points r 0 . 6 A set of vector OPs k are constructed as follows.…”
Section: Macromolecular Opsmentioning
confidence: 99%
“…In this view, macromolecular structural dynamics follows from the coupling of processes across multiple scales in space and time. [2][3][4][5][6][7][8][9][10][11] The result of the multiscale analysis of the Newtonian Liouville equation is a set of Langevin equations of stochastic OP dynamics. If the set of OPs is incomplete (i.e., their dynamics is coupled to that of other slowly changing variables), then they satisfy equations involving time delays (i.e., memory effects) as resulting from traditional projection operator analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Even single membrane proteins in the native lipid environment can be studied. Simulations of large biomolecular systems are becoming more feasible as demonstrated by the work on the MD-based structure prediction of the ribosome complex from E. coli (Villa, 2009), the simulation of the assembly of lipids and proteins into lipoprotein particles (Shih, 2007), the MD studies of viral capsid self-assembly (Freddolino, 2006;Miao, 2010) and vesicle fusion simulations (Kasson, 2010). MD simulations are used to gain information about the conformational changes of protein structure, i.e.…”
Section: Model Of V2 Receptormentioning
confidence: 99%